2015
DOI: 10.1186/s13014-015-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal proton MR spectroscopy as a novel approach in the assessment of radiation injury and the correlation to neurocognitive function impairment: initial experiences

Abstract: BackgroundThe hippocampus is considered as the main radiosensitive brain structure responsible for postradiotherapy cognitive decline. We prospectively assessed correlation of memory change to hippocampal N-acetylaspartate (h-tNAA) concentration, a neuronal density and viability marker, by 1H-MR spectroscopy focused on the hippocampus.MethodsPatients with brain metastases underwent whole brain radiotherapy (WBRT) to a dose of 30 Gy in ten fractions daily. Pre-radiotherapy 1H-MR spectroscopy focused on the h-tN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…1 H-MRS has been used to evaluate hippocampal brain metabolites in various populations, including patients with mild cognitive impairment, 17 patients with Alzheimer’s disease, 18 cognitively normal older adults, 19 and patients receiving whole brain radiotherapy. 20 Results of these studies show hippocampal brain metabolites to be reliable preclinical markers of cognitive and memory function.…”
Section: Introductionmentioning
confidence: 99%
“…1 H-MRS has been used to evaluate hippocampal brain metabolites in various populations, including patients with mild cognitive impairment, 17 patients with Alzheimer’s disease, 18 cognitively normal older adults, 19 and patients receiving whole brain radiotherapy. 20 Results of these studies show hippocampal brain metabolites to be reliable preclinical markers of cognitive and memory function.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal avoidance WBRT (HA-WBRT) has been the most widely accepted used method to mitigate the adverse neuro-psychologic effects of WBRT (15)(16)(17). It is however essential to understand the basis of patient selection for HA-WBRT (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…It is finally worth mentioning about the search for objective methods for assessing cognitive impairment in patients with post-cerebral RT. In a proton MR spectroscopy study on patients that had undergone WBRT 4 months earlier, reduced concentrations of N-acetylaspartate were noted; this being a metabolite of nerve tissue from the hippocampal region [87]. Another study using MR spectroscopy found sub-acute radiation damage to nerve tissue after a month post-WBRT [88].…”
Section: Hippocampal Sparing In Patients Irradiated Electively or Thomentioning
confidence: 99%